ANALISIS PENGARUH POLA ASUH ORANG TUA TERHADAP PERILAKU SOSIAL ANAK DI SEKOLAH DASAR - Gaol, Rumiris Lumban; Ana, Juli; Tanjung, Darinda Sofia (Universitas Negeri Medan, 2024)
The process of life begins with the family, and the process is different in every family. In general, a child's personality is a reflection of the family. Having a good personality requires a long process, and requires good cooperation between members. A good personality usually starts from good habits from an early age that start from parental parenting, and along with the passage of time, good habits will become a character and become part of a child's personality. The growth of a child's character is determined by the assistance of parents through the parenting style that is given every day in their lives. The better the parenting style, the better the social growth of a child. The purpose of this study is to see how the parenting style of children and how the parenting pattern affects the social behavior of children. This research method is a quantitative type of survey. The results were found through questionnaire data on the type of parenting and children's social behavior. The type of parental parenting that is dominant in children is permissive parenting, which tends to give freedom to children.